A segurança alimentar e nutricional e o desenvolvimento da agricultura familiar: um estudo na comunidade da Península do cavernoso no município de Candói-PR - Pereira, André Alves (2014)
Nowadays, the issue of food and nutrition security, and their connection to family farming, permeates aspects of rural development. Thus, family farming is perceived as a field of social reproduction, consisting of a multi-functionality, which includes social, environmental factors and production, that jointly drive the agriculture beyond the productive factor. Therefore, this thesis has the overall objective to understand the contribution of food and nutrition security for the development of family agriculture in the Community Península do Cavernoso in Candói - PR . For this, we used a theoretical reference that deals with the family farming, distinguishing it from the peasant style, with readings that comprise the issue of development in its multiple dimensions and with an emphasis on rural and sustainable development. The research focused on identifying the issue of food production, previous food and nutritional security programs in order to point out how these programs contribute to the development of the families. Thus, the composition of the food agenda gathers all the food that is commercialized by them, as well as the food produced for their own consumption. There are 79 families in the community, 24 were selected for the survey. It was revealed that food and nutrition security is corrupted by the impact of programs such as PAA and PNAE and food production with the center in the families and the development that is adjacent to food issue.